Micronutrients and pregnancy; effect of supplementation on pregnancy and pregnancy outcomes: a systematic review - Zerfu, Taddese Alemu (BioMed Central, 2013)
INTRODUCTION: Every year more than 20 million infants are born with low birth weight worldwide. About 3.6 million infants die during the neonatal period. More than one third of child deaths are thought to be attributable to maternal and child under nutrition. OBJECTIVES: To systematically review the effect of supplementing various combinations and types of micronutrients on the course and outcomes of pregnancy. METHODS: Electronic search of Medline, Pub Med, Health Internetwork access to Research Initiative, and Google Scholar databases was conducted. Outcomes of interest were birth weight, low birth weight, small size for gestational age, prenatal mortality and neonatal mortality. After exclusion of irrelevant /incomplete ones, 17 out of 115 articles were considered for the final analysis. FINDINGS: Majority of the articles reviewed favored the supplementation of micronutrients to pregnant mother. Some studies suggested calcium supplementation is associated with a significant protective benefit in the prevention of pre-eclampsia. The remaining articles reviewed, showed significant benefit of Multiple Micronutrients supplementation during pregnancy in reducing low birth weight, small for Gestational Age births as compared to the usual iron-folate supplements. CONCLUSIONS: Supplying micronutrients, mainly multiple micronutrients have beneficial effect in reducing the risk of low birth weight and other complications. Further studies at various combination and doses of micronutrient supplements are recommended.